Copper aluminate spinel by soft chemical routes. Issue 1 (January 2016) - Mindru, Ioana; Gingasu, Dana; Patron, Luminita; Marinescu, Gabriela; Calderon-Moreno, Jose Maria; Preda, Silviu; Oprea, Ovidiu; Nita, Sultana
Abstract: Copper aluminate spinel (CuAl2 O4 ) was obtained by two different chemical routes: the precursor method and the solution combustion method involving glycine-nitrates. The polynuclear complex compounds: (NH4 )2 [CuAl2 (C4 O6 H4 )3 (OH)4 ]·2H2 O (I ), (NH4 )[CuAl2 (C6 O7 H11 )3 (OH)6 ]·2H2 O (II ) and [CuAl2 (NH2 CH2 COOH)4.5 ]·(NO3 )8 ·4H2 O (III ) were characterized by elemental chemical analysis, infrared spectroscopy (IR), ultraviolet–visible spectroscopy (UV–vis) and thermal analysis. The final oxide powders were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), IR, Raman spectroscopy (RS), UV–vis and photoluminescence (PL) spectroscopy. X-ray diffraction patterns indicated the formation of the cubic phase CuAl2 O4 with good crystallinity. The crystallite size ranged from 18.70 to 19.50 nm. Electron microscopy revealed the morphology corresponding to the complete crystallization into CuAl2 O4 . The band gap values ranged between 1.97 and 2.03 eV. The photocatalytic degradation of methyl orange (MO) was investigated using copper aluminate as catalyst.